Fatherless in Perspective Family Philosophy: Can it Undermine a Child's Motivation to Learn? - Karnadi; Latifatus Maulida (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2025)
This study aims to examine the impact of the fatherless phenomenon on children's learning motivation from the perspective of family education philosophy. Secondary data were analyzed through a review of the relevant literature. The theoretical framework of this research is based on the thoughts of John Dewey, Abraham Maslow, and Carl Rogers regarding the role of the family in character formation and intrinsic motivation. The results of the study show that the absence of a father figure can significantly reduce children's motivation to learn due to the psychological, social, and economic challenges faced. Lack of emotional support, difficulties in social interaction, and limited educational resources are inhibiting factors. However, the research also highlights the importance of the role of mothers and the surrounding environment in providing support, as well as strengthening family values as capital to build positive learning motivation in fatherless children. The implications of this study emphasize the need for comprehensive and collaborative interventions between families, schools, and communities. Counseling, mentoring, use of educational technology, and economic empowerment programs for single families are recommended as strategies to support the academic and social-emotional development of fatherless children, so that they can reach their maximum potential even in the condition of an incomplete family.